Peran Pelayanan Gembala Terhadap Pertumbuhan Rohani Pemuda di Gereja JKI Injil Kerajaan Satelit Majapahit Semarang - Sudjono Sudjono; Stephanus Karnadhi; Fibry Jati Nugroho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Spiritual growth of Youth is the process of growing in size or growing in the spirituality and context of Christianity. Spiritual growth involves trying to guide individuals who do not yet have a personal attachment to Jesus Christ toward a connection with Him, so that they can become part of God's responsible community [Latif Helen Farida,